Pengaruh Persepsi Harga Dan Tingkat Kepercayaan Terhadap Keputusan Pembelian Pada Mahasiswa Pengguna Shopee Di Kota Malang - Dyah Putri Anggraini; Nur Hidayati; Ita Athia (E-JRM : Elektronik Jurnal Riset Manajemen, 2022)
Abstract This study aims to analyze the effect of price perception, and the level of trust in purchasing decisions on shopee users in Malang city. The population in this study are students who use shopee in the city of Malang. This research includes explanatory research with a quantitative approach. The sampling used is purposive sampling, with a sample of 65 respondents. Data collection techniques using questionnaires via google form. The population in this study were students at the Islamic University of Malang, University of Muhammadiyah Malang, State University of Malang. The results of the study partially show that price perceptions affect purchasing decisions, the level of trust affects purchasing decisions.  Keywords: Price Perception, Trust Level, Purchase Decision